Improving athletic performance: is altitude residence or altitude training helpful? - Fulco, C. S.; Rock, P. B.; Cymerman, A. (Aviation, Space, and Environmental Medicine, 2000)
Exercise training studies conducted at different altitudes (1250-5700 m) of varying durations (30 min to 19 wk) are critically reviewed to determine the efficacy of using altitude as a training stimulus to enhance sea level and altitude exercise performance. Four strategies are discussed: a) exercise training while residing at the same altitude; b) exercise training at altitude but residing at sea level; c) exercise training at low altitude but residing at a higher altitude; and d) exercise training under sea level and altitude conditions but only after altitude acclimatization has occurred. Residing at altitude causes a multitude of potentially beneficial physiological, ventilatory, hematological and metabolic changes that theoretically should induce a potentiating effect on endurance exercise performance. While it is accepted that endurance performance is greatly enhanced at altitude, there is less support for the view that altitude training while residing at altitude improves subsequent sea level endurance performance. There is some evidence, though also not universally accepted, that training at altitude but residing at sea level may benefit sea level endurance performance. Most recently, the combination of "living high" (e.g., at 2500 m) to obtain beneficial physiological changes associated with altitude acclimatization and "training low" (e.g., at 1250 m) to allow maintenance of high-intensity training is accumulating scientific and popular support as the most advantageous strategy to improve subsequent sea level exercise performance in well-trained, competitive runners. Volltext unter: https://www.academia.edu/18352260/Improving_athletic_performance_Is_altitude_residence_or_altitude_training_helpful